Educational and Employment Patterns in Serious Adolescent Offenders With Mental Health Disorders: The Importance of Educational Attainment - Schubert, Carol A. (Criminal justice and behavior, 2018)
This study examines employment and educational outcomes for justice-involved adolescents with and without mental health disorders in the Pathways to Desistance study. We examine the patterns of education and employment and the effects of several factors, including the presence of a mental health disorder, on these positive outcomes. Three findings emerge: (a) youth with mental health problems have a relatively high number of other criminogenic risk factors, (b) education and employment patterns do not differ by disorder status, and (c) the presence of a mental health disorder is not independently linked to poorer employment outcomes, but educational achievement is. These analyses provide information needed to target services for these adolescents in the juvenile justice system, who are at high risk for poor educational and employment outcomes. Results indicate a need for increased emphasis on higher levels of academic attainment as a way to promote positive employment outcomes in these youth.